Seramik birleştirme teknolojisi ve yapısal seramiklerin lehimlenmesi - Akkoca, Osman (Fen Bilimleri Enstitüsü, 1994)
Son yıllarda seramik, malzemelerin içten yanmalı motorlar, türbin motorları ve ısı eşanjörleri gibi yapısal uygulamalarda kullanımlarına olan ilgi artmıştır. Yüksek performanslı yapısal seramikler (AljOj,SİC,SijN<,ZrOj v.b.) yüksek, mukavemet ve bu mukavemetlerimi yüksek sıcaklıklarda koruyabilme, sertlik, boyufesal kararlılık, iyi korozyon ve erozyon direnci, yüksek elastiklik modülü ve düşük kütle yoğunluğu gibi birtakım süper özelliklere sahiptirler. Seramik malzemelerden karmaşık monolitik şekiller oluşturmak zordur ve bir çok yapısal uygulamada kırılgan seramik, malzemelerin sünek metal malzemelere birleştirilmesi gerekmektedir. Bu tür sınırlamalar ve gereksinimler seramik-seramik ve seramik-metal birleştirme teknolojisine olan ilgiyi artırmıştır. Seramik birleştirmeler için lehimleme, difüzy on kaynağı, yapıştırma ve mekanik tutturma gibi birçok teknik uygulanabilir nitelikte olmakla birlikte, en ilgi çekici tekniklerden birisi lehimlemedir. Gelişmekte olan bir teknoloji olması nedeniyle, bu çalışmada bir literatür araştırması yapılmıştır, öncelikle, lehimleme tekniği hakkında detaylı bilgi verilmiştir ve diğer teknikler de literatüre yansıdığı ölçüde değerlendirilmiştir- ilave olarak,, seramik bağlantıların tahribatla ve tahribatsız muayeneleri hakkında bilgi verilmiştir. Sonuç bölümünde ise literatür araştırması neticesi ortaya çıkan ortak bulgular özetlenmiştir.

Structural ceraraics is an emerging class of engineering materials with a variety of current applications and with the potential for much wider application, especially at high temperatures. High- performance structural ceraraics uniguely combine strength, strength retention at high temperatures, hardness, dimeusioaal stabillty, good corroaion and erosion. behavior, high elastic modulus, and low mas s density. Monolithic struc-tural ceraroics are currently based primarily on ailicon carbide, silicon nitride, partially stabilized zirconium dioxide, ör alumina, With the current intereat in using ceramica as structural components in such demanding applications as internal combustion engines, türbine engines, and heat exchangers, there has come a heightened interest in ceramic joining technologies. The reasons for the interest in joining ceraroics are the same as those for joining metals; however, the devolepment of effective ceramic joining technigues could have a rauch greater impact on the ir us e in mass-produced components. Öne of the most important functions of joining technigues is to provide the means for economic fabrication of complex, multicomponents structures. Devolepment of effective ceramic joining technigues will be especially significant because of l imitations imposed on component manufacturing by ceramic processing technigues and by the materials themselves. For example, deformation of densified ceramics to form complex shapes is practically impossible because of the fact that most ceramic materials are brittle even at elevated temperatures. Ceramics are also costly to machine. By reducing the co«plexity of indivudual parts, significant savings in machining coat can be expected. Similarly, in most structural applications brittle ceramic materials have to be joined to ductile metal materials. Effective ceramic joining technigues can also play an important role in improving the reliability of ceramics structures. Because ceraraics are brittle materials, they are very sensitive to flaws, due to guality of raw materials used in their production and to the - characteristics of various processing technigues, including machining. A single flaw can cause the rejection, ör, if undetected, the failure of ceramic part. Rather than dealing with complicated monolithic parts, it is easier to inspect and detect f laws in simple-shaped components before they are joined to form complex atructures. There are many technigues that could be used to make ceramic-ceramic ör ceramic-metal joints ranging from f asi on we l di ıxg through di f f us i on honding, brazing and adh.es i ve bonding to mecbanical attacbment but brazing is öne of the raost attractive, Thus, the relative toughness of braze metals and ailoys permit some accommodation of tbe thermal contraction mismatch strains generated as dissimilar workpieces are cooled from the bonding temperature, Further, brazing furnaces are readily availahle on the long established practice of brazing metal workpieces gives some confidence that brazes can be used to join ceramic workpieces. in this study, the teenniques potentially available to make ceramic-ceramic ör ceramic-metal joints were reuieved and particularly, brazing was examined in detail. Additionaly, some informations were given about destructive and non-destrtıctive evaluation of ceramic joints. Fusion welding with technigues such as are welding, electron beam welding,ör laser welding, is not generally applied to tne joining of ceramics, and, conseguently, there are few published reports on this subject, There are a number of mechanical and pbysical properties that make fusion velding of ceracaics diffucult. By having limited ductilities, ceramics have little r es is tane e to cracking as a result of thermal stresses produced by fusion welding operations. Another important property f ör fusion welding is melting, which is an inherent reguirement of the process. Many structural ceramics like SiC and SijM* sublime instead of melting. Others like AlıOj have relatively high vapor pressure of their melting temperatures, «rhich contributes to excessive fusion zone porosity. Mechanical attachment of ceramic to »etals is readily achievable using press-fitting and shrink-fitting. However, mechanical attachment is not a generally attractive process for joining structural ceramics because of the freguent necessity for introducing intrusive stress- raising features such as threads ör bol t hol es, and the low strenght and lack of herraeticity of the joints. A direct bond betvreen the «rorkpieces is reguired for many appli cations. Adhesive bonding has some advantages över fusion welding and some mechanical attachment processes. it leaves the vrarkpieces substantially unaffected by the joining process. However, many of the potential applications for ceramic-metal systems reguire the joints to withstand high stress, high temperatures ör chemically ardous environments, conditions unsuitable for adhesives used in commercial practice at present- Joining by ceramic processing technigues is taken to mean the joining of ceramics by techniques normally used för pruducing monolithic ceramic bodies. This definition is meant to include processing seneme 3 like the us e of slip interlayers as filler raaterials. and höt pressing of green bodies to simultaneously densify and join ceramic parts. The application of these techniques can be coroplicated relative to more conventional joining technigues such as brazing, and can reguire considerable eacpertise. Ceramic processing technigues, however, can produce excellent joints in parts of çoraplex shapes. Diffusion bonding is a near net shape joining technigue which is particularly suited to applications reguiring high degrees of accuracy. Ali constituents in the process are solid, and hence a low w ör k of adhesion may result in the formation of a good joint by diffusion bonding. in addition, diffusion bonding method allows the simultaneous manufacture of many bonds in a complex joint configuration by stacking thin strips of material and subjecting the assembly to bonding conditions. Another potential advantage of diffusion bonding över brazing is that alloys with comparatiyely low melting point do not have to be used as fillers for ease of fabrication as those in brazing, and hence the inherent upper temperature is high. This process is re l at i ve l y simple when two identical materials are to be joined, but when joining dissimilar materials there are many potential complications. Brazing is an attractive method for incorporating high temperature structural ceramics in engineering systems, However, structural ceramics are among the most stabie compounds known, as a result of their chemical stability is that they are wetted only with difficulty by liguid metals. The prime reguirement of a braze is that it should wet workpieces, that is, it should be able to spread över their surface and enter narrow, capillary, gaps between components to be bonded. Htetting of ceramics surfaces can be obtained by three general methods: 1. Using of braze glasses : Glasses, particularly those used to assist densification during sintering, also have the potential to be used for joining ceramic parts. Öne advantage of using these glass materials as filler metals for joining is that chemical compatibility with the parent ceramic is generally assured- Other advantages are that the viscosity, flaw properties, and melting characeristics of glasses can be controlled över wide ranges, and that adherence of the glasses to the ceramics is usually guite good. Another desirable feature of glasses is that many compositions can be crystallized to iroprove their meçhanical and corrosion properties. However, the brittleness nature of glasses an4 their sensitivity to the thermal expansion mismatch between to be joined materials restrict their using as filler metals in brazing ceramic materials. 2. Metallizing of ceramic surfaces prior to brazing: A variation of the metallizing approach is the us e of vapor deposited coating of metal s to promote the «retting of ceramics. The key element of the process is the deposition of a thin coating, general ly of a reactive metal such as titanium, onto ceramic surfaces prior to brazing. This metallizing approach can be applied to both oxide ceramics and non-oxide ceramics. Uowever, it appears that this technigue has not been widely exploited for practical purposes. The most widely used metallization process for oxide ceramics is that in which mixtures of a glassy phase and a refractory metal are applied as paint by brushing ör screen printing, as exemplified by the "moly-manganese" process. The prime purpose of the glassy phase is to bond the refractory metal to the ceramic oxide, while that of the refractory metal is to render the surfaçe amenable to electroplating and ultimately brazing to effect a joint. The coated ceramic is then fired in wet hydrogen at a temperature near 1500 °C, which causes the glassy mat er ia l to densify the metal l iç l ay er and to bond it to the ceramic surface. Ceramic surfaces metallized by the Mo-Mn process can be brazed with a number of conventional braze filler metals- Suçcesful completion of the process depends on factors such as the manufacture and properties of the ceramic, and the composition of the metallizing paint, its application, subseguent firing and further treatment. Minör variations from the established process conditions and procedures can have disastrous effects on the guality of the product. 3. Alloying braze filler metals with elements that activate wetting: The active filler metal process incorporates an active metal, usually titanium, into filler metal. During the brazing cycle, the titanium segregates to the ceramic surface vrhere it reacts to form a wettable surface. Altough the range of materials suggested by laboratory studies is large, the number of braze alloys that are commercially available is far more restricted. The longest established active metal braze is the Ag,28Cu eutectic to which several percent of titanium has been added mechanically to produce sandwich sheets ör cored wires. High titanium concentrations can result in the formation of thick fragile reaction product layers, so in practice ternary and more complex alloys in which titanium is relatively insoluble are used to braze ceramic materials. To produce such alloys indium and tin are generally added to the binary brazes. «hile brazes using the reactivity of titanium to induce the wetting of ceramics are the most thoroughly developed and widely used, they are not the only materials that have been considired ör evaluated. in particular, aluminium and its alloy have been studied as potential brazes for silicon ceramics and now attention is being given to the use of nickel brazes when silicon ceramics are considered for high temperature applications. Active metal brazing can be used to produce high-integrity ceramic-ceramic and ceramic-metal joints. However, wetting and bonding are not synonymous, and hence considerable care is needed in the selection of the brazing alloy on fabrication conditions. Many factors must be taken into consideration in choosing the fabrication conditions to be employed to braze a ceramic component. The selection of surface cleaning and preparation processes, the environment and the thermal cycle are the most important ones. The main problem in joining ceramics to metals is the thermal expansion mismatch between the ceramic and the metal. Typically, metals have higher coefficients of thermal expansion than ceramics, and cracking of the ceramic occurs upon cooling the joint from the joining temperature. To overcome of this problem, suitable ceramic-metal-braze systems should be selected. In most cases, this is not practical; the particular ceramic and metal components of the joint are selected based on other properties, such as strength or chemical inertness. Another way to minimize the thermal expansion mismatch is to use an inter layer - Bond strength measurements provide information on the mechanical quality and integrity of joints. They can employ either conventional or fracture mechanics testing techniques. In conventional bend, shear and tensile tests, the stress to fracture the bonded surfaces is used to characterize a bond strength. In fracture mechanics approach, the mechanical quality of a joint is characterized principally by the fracture energy, but other useful measures are the fracture toughness and compliance. Techniques for the non-destructive evaluation of ceramic joints have yet to be widely used. This reflects basic difficulties in detecting flaws at interfaces between dissimilar materials where property changes are marked. As ceramic materials are generally non-magnetic and non- conductive, the methods which have shown the most promise have in the main been developments or refinements of well- established processes based on acoustics or X-rays. Recently, however, techniques exploiting the properties of thermal waves have shown considerable potential for the NDE of ceramics joints. The results obtained in this study can be summer ized as follows; 1. The technology of joining ceramic for structural applications not related to electronic industry is largely in a development stage. xiv 2. Ceramic joining techniques have generally been practiced on oxide ceramics, particularly alumina. However, recently, the interest in joining non-oxide ceramics have been increased due to their increasing applications in technical structures, 3. The main problem with the ceramic joining technology is that there are no standarts for describing ceramic techniques or their use for specific materials on applications. Another area where standarts are lacking is in the strength testing of ceramic joints. For this reason, direct comparision of test data from different studies should only be done when each has used the same testing techniques and the same identically prepared specimen sizes.
Ceramic foining technology and brazing of structural ceramics
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Lehimleme; Motorlar; Seramik endüstrisi; Soldering; Motors; Ceramic industry